Brain Response to Primary Blast Wave Using Validated Finite Element Models of Human Head and Advanced Combat Helmet - Zhang, Liying; Makwana, Rahul; Sharma, Sumit (Frontiers in Neurology, 2013)
Blast-induced traumatic brain injury has emerged as a “signature injury” in combat casualty care. Present combat helmets are designed primarily to protect against ballistic and blunt impacts, but the current issue with helmets is protection concerning blasts. In order to delineate the blast wave attenuating capability of the Advanced Combat Helmet (ACH), a finite element (FE) study was undertaken to evaluate the head response against blast loadings with and without helmet using a partially validated FE model of the human head and ACH. Four levels of overpressures (0.27-0.66 MPa) from the Bowen’s lung iso-damage threshold curves were used to simulate blast insults. Effectiveness of the helmet with respect to head orientation was also investigated. The resulting biomechanical responses of the brain to blast threats were compared for human head with and without the helmet. For all Bowen’s cases, the peak intracranial pressures (ICP) in the head ranged from 0.68-1.8 MPa in the coup cortical region. ACH was found to mitigate ICP in the head by 10-35%. Helmeted head resulted in 30% lower average peak brain strains and product of strain and strain rate. Among three blast loading directions with ACH, highest reduction in peak ICP (44%) was due to backward blasts whereas the lowest reduction in peak ICP and brain strains was due to forward blast (27%). The biomechanical responses of a human head to primary blast insult exhibited directional sensitivity owing to the different geometry contours and coverage of the helmet construction and asymmetric anatomy of the head. Thus, direction-specific tolerances are needed in helmet design in order to offer omni-directional protection for the human head. The blasts of varying peak overpressures and durations that are believed to produce the same level of lung injury produce different levels of mechanical responses in the brain, and hence "iso-damage" curves for brain injury are likely different than the Bowen curves for lung injury.